Developing New Capabilities across a Supplier Network through Boundary Crossing: A Case Study of a China-Based MNC Subsidiary and its Local Suppliers. Issue 3 (March 2013) - Hong, Jacky F. L.; Snell, Robin Stanley
Our nested case study shows how a China-based focal subsidiary of a Japanese MNC used various power bases to orchestrate a co-opetitive and diverse supplier ecosystem, and to drive cumulative cycles of collaborative capability development involving successive phases of capability gap articulation, evolution and institutionalization. All phases of capability development required the crossing of cognitive boundaries, which was facilitated by mutual engagement with boundary objects, and by common possession of generic background knowledge disseminated by the focal firm. The capability evolution phase also required the crossing of social and governance boundaries, which was supported and legitimized by shared framing assumptions about mutual benefit and continuous development, while the capability institutionalization phase also required the crossing of governance boundaries. Although the focal firm was open to suggestions for mutual benefit, it exercised unilateral control over design decisions, thereby pressurizing its suppliers to engage in capability development to meet specifications that they found arduous. Supplier diversity was a resource, and co-opetition a driving force for the discovery of solutions to manufacturability problems during the capability evolution phase, such that failure to develop requisite capabilities was uncommon.